The Chilean exception: racial homogeneity, mestizaje and eugenic nationalism. - Walsh, Sarah (Journal of Iberian & Latin American Studies, 2019)
Scholarship on race in Latin America has overwhelmingly characterized racial mixture as a unique feature of the political and social landscape there. Studies of eugenics in Latin America especially highlight the relative pragmatism regarding race mixing in contrast to eugenics elsewhere. However, an acceptance of race mixing did not preclude the persistence of racial hierarchy among Latin American racial theorists. Examining the development of eugenics in Chile, this article reveals how notions of racial plasticity existed alongside that of racial superiority. Specifically, it contends that Chilean racial exceptionalism in the early twentieth century was predicated on the idea that some types of racial mixture were better than others. Conveniently for Chileans, their mostly indigenous and European ancestry was one such preferred combination. Yet, racial mixing was only desirable insofar as it resulted in a homogeneous national population. This combination of ideas functioned much like white supremacy in other parts of the world. Using historical texts, popular and medical periodicals, and visual images produced between 1900 and 1950, this paper will demonstrate how race science in Chile reconciled the nation's history of racial mixture with its claims to racial homogeneity and superiority relative to the rest of Latin America.